Challenges and Prospects of Islamic Education Institutions and Sustainability in The Digital Era - Abas Hidayat; Siti Fatimah; Didin Nurul Rosidin (Nazhruna: Jurnal Pendidikan Islam, 2022)
Educational institutions are places for educational activities that aim to change lives for the better. The development of digital technology requires educational institutions to establish and develop the education system continuously. This article explores the challenges and prospects of Islamic educational institutions and their sustainability in the digital technology era. The method used for this article is the qualitative inductive content analysis method. The findings are 1) Political changes, economic changes, and socio-cultural changes in society require Islamic education institutions to upgrade the institutional system and control all institution's activities. 2) Islamic education institutions' prospects include improving human resources and service quality, effectiveness and efficiency of financial management, and emphasizing promotion costs. 3) The future of Islamic education institutions, namely the sustainability of the institution's existence, the sustainability of the quality level of the institution, and the sustainability of invested resources.